2022
DOI: 10.3390/biom12070921
|View full text |Cite
|
Sign up to set email alerts
|

Monoterpenes as Sirtuin-1 Activators: Therapeutic Potential in Aging and Related Diseases

Abstract: Sirtuin 1 (SIRT) is a class III, NAD+-dependent histone deacetylase that also modulates the activity of numerous non-histone proteins through deacylation. SIRT1 plays critical roles in regulating and integrating cellular energy metabolism, response to stress, and circadian rhythm by modulating epigenetic and transcriptional regulation, mitochondrial homeostasis, proteostasis, telomere maintenance, inflammation, and the response to hypoxia. SIRT1 expression and activity decrease with aging, and enhancing its ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 127 publications
0
2
0
Order By: Relevance
“…Therefore, they are considered promising targets for the development of therapeutic strategies to halt or, at least, slow down the progression of those diseases. In this regard, many natural compounds have been found to have positive effects in in vitro and in vivo models of many diseases by inhibiting those processes [ 8 , 9 , 34 ] and/or activating anti-inflammatory pathways such as Nrf2 and SIRT1 [ 35 , 36 , 37 ]. The results obtained in this study suggest that (R)-(-)-carvone may be useful by targeting the interaction between inflammatory and anti-inflammatory/antioxidant signaling pathways and intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they are considered promising targets for the development of therapeutic strategies to halt or, at least, slow down the progression of those diseases. In this regard, many natural compounds have been found to have positive effects in in vitro and in vivo models of many diseases by inhibiting those processes [ 8 , 9 , 34 ] and/or activating anti-inflammatory pathways such as Nrf2 and SIRT1 [ 35 , 36 , 37 ]. The results obtained in this study suggest that (R)-(-)-carvone may be useful by targeting the interaction between inflammatory and anti-inflammatory/antioxidant signaling pathways and intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of circFOXO3 is involved in cellular senescence in the CNS, which may lead to neurodegeneration; however, a controversial report has shown that expression levels of circFOXO3 are significantly decreased in the blood of elderly persons and in late passage primary culture cells [51]. CircPVT1, a circular form of an exon of PVT1, influences cellular senescence and neurodegeneration by changing the expression levels of let-7 and miR-199-5a: let-7 regulates immune response, autophagy, and apoptosis [52][53][54], whereas miR199-5a regulates the expression levels of sirtuin1 (SIRT1) mRNA, which is associated with brain aging and neurodegeneration resulting from the dysregulation of mitochondrial energy metabolism [55][56][57][58]. Epigenetic modifications, such as DNA and RNA methylation, influence chromatin function, and their age-related changes are associated with brain aging and neurodegeneration [14].…”
Section: Age-related Changes Of Circrnas and Rna Editingmentioning
confidence: 99%